Validation of educational technologies in health care: scoping review protocol (Research, Society and Development, 2021)
This manuscript presents the scope review protocol which aims to map the validation process of educational technologies in the health field. This review wiil be conducted according to Joanna Briggs Institute (JBI) guidelines and will be previously registered in the Open Science Framework repository. Guided by the survey question: How has validation process of educational technologies in the health field been taking place? The survey will occur in eight database. It will be utilized the Rayyan Software for managing selection and collection of studies. Based on inclusion and exclusion established criteria, two independent reviewers will perform the title and abstract reading of all identified studies. In case of divergences between the reviewers, a third reviewer will be requested. The data will be extracted, summarized and descriptively presented, making use of frames and images, as indicated in the checklist proposed by PRISMA-ScR. We expect this protocol enables a scope review with a consistent methodology and from it, greater knowledge and guidance concerning validation process of educational technologies in the health field.